(untitled) (Global Journal of Human-Social Science, 2012)
As a compulsory course of law specialty in China s online higher diploma education online education course of constitution has the features that meet the necessity of distance education in the Internet age as well as the basic requirements of constitutional course teaching to be a vital way to perfect the constitutional course teaching The springing up of various network media technology and the lower demands for the software and hardware in learning the course provides the indispensable components for the realization of constitutional online education course The design of teaching technique environment teaching structure teaching contents and the evaluation of teaching quality is the elemental path for constructing constitutional online education course